Portopulmonary Hypertension - Krowka, Michael J. (Seminars in Respiratory and Critical Care Medicine, 2012)
Portopulmonary hypertension (POPH) refers to the presence of pulmonary arterial hypertension (PAH) in patients with portal hypertension. Pulmonary hypertension in patients with liver disease or portal hypertension can be due to multiple mechanisms, including hyperdynamic (high-flow) state, increased pulmonary venous congestion, and vascular constriction or obstruction of the pulmonary arterial bed. Vascular obstruction to pulmonary arterial flow, reflected by increased pulmonary vascular resistance (PVR), is a key parameter that defines POPH. Among patients with portal hypertension, reported incidence rates of POPH range from 2 to 9%. Long-term survival in cases of POPH is poor. Favorable responses to pulmonary vasodilator/vasomodulatory therapy have been observed, but prospective, randomized trials are lacking. Severe POPH with right ventricular failure despite vasodilator therapy is associated with poor outcomes in the setting of liver transplantation (LT) and is considered a contraindication to LT. The post-LT course of patients with moderate POPH is unpredictable, but most patients can be weaned from PAH-specific therapy over time.
Keywords: portopulmonary hypertension; pulmonary hypertension; portal hypertension; liver transplant